The Metallurgical hydrogen as an indicator and cause of damage to rolled steel: Hydrogen diagnostics of fracture (Fracture and Structural Integrity, 2022)
Fatigue tests and measurements of the volumetric distribution of metallurgical hydrogen in specimens cut from rolled I-beam 60Sh3 made of steel 10KhSND were carried out. Fatigue tests show a 20% reduction in fatigue limits compared to similar sheet material. On the fractures of the samples, there are flock-like defects in the areas of interface of the flanges of the I-beam, or the so-called zones of difficult deformation. The concentration of metallurgical hydrogen is unevenly distributed and varies from 0.17 ppm to 1.8 ppm. Large concentrations of hydrogen are observed in the zones of difficult deformation, which indicates the hydrogen nature of the metal defects observed at the fracture. The result of mechanical tests and hydrogen diagnostics is a manufacturing defect of rolled products that cannot be corrected. Hydrogen diagnostics using metallurgical hydrogen (without hydrogen charging samples) takes tens of times less time than mechanical tests, and gives an adequate result.
Keywords: I-beam; Fatigue; Hydrogen diagnostics; Metallurgical hydrogen